Kinesin-propelled label-free microtubules imaged with interference reflection microscopy. (17th September 2020) - Saper, Gadiel; Hess, Henry
Abstract: Interference reflection microscopy (IRM) utilizes the interference between the light reflected from the surface and the light reflected from an object to generate contrast and can be used to image nanometer size objects, such as a microtubule adhered to a surface as demonstrated by Mahamdeh et al . In in vitro gliding motility assays and in a variety of nanodevices, cytoskeletal filaments are propelled by surface-adhered motor proteins 20 to 50 nm above the surface. Here we employ IRM to image kinesin propelled label-free microtubules and show that these unlabeled microtubules are longer and move at higher velocities compared to rhodamine-labeled microtubules. IRM also provides information about the distance of an elevated microtubule from the surface and is used by us to follow microtubules crossover events. Finally, we perform the gliding assay without adding an oxygen scavenging system and show that there is significantly less photodamage for label-free microtubules measured with IRM compared to rhodamine-labeled microtubules imaged with fluorescence microscopy. This result suggests that IRM can be used for future experiments to further explore the effect of oxygen radicals on the gliding assay. Moreover, the increased velocity and length make label-free microtubules desirable for engineered devices based on molecular motors and filaments.